(untitled) (Iraqi Journal of Medical Sciences, 2018)
Background: Human Adenovirus (ADV) is one of highly prevalent viruses worldwide, after primary infection, it remains latent and then might reactivate in immunocompromised patients. High ADV viremia seen in renal transplant recipients (RTR) with clinical presentations range from asymptomatic viremia to respiratory and gastrointestinal disease hemorrhagic cystitis, graft dysfunction and severe disseminated disease. Objective: The objectives of this study are to determine the rate of occurrence of ADV viremia by quantitative Real time PCR (QRT-PCR) in RTR and correlate them with urine cytology results, renal function tests and patients’ hematological parameters. Methods: Seventy-one renal transplant recipients (RTR) were enrolled in this study. Whole blood samples (3 ml) divided into two parts, one part for complete blood picture and differential count and other part from which plasma separated and subjected to viral DNA extraction and then ADV Taqman QRT-PCR analysis for viral load measurement. Five ml urine specimens were collected for Pap-stained urine cytology. Results: Out of 71 RTR, 15 (21.12%) had positive ADV viremia by QRT-PCR, with a mean viral load 4.0 x107± 1.9 x108 copies/ml, and 80% (12 out of the 15) of positive viremia patients aged more than 40 years (p=0.011). All of RTRs 15/15 (100%) had symptomatic urinary tract infection (UTI) (p=0.039), and 5 out of 9 patients who had lymphopenia had positive viremia (p=0.007). Pap-stained urine cytology smears showed that 39/71 (55.71%) of the RTRs had positive decoy cells (DC), but there was no significant correlation between ADV viremia and the presence of DC (p=0.107). Conclusion: The present study showed the prevalence of ADV viremia in RTRs, with very high viral load, which is associated with lymphopenia and overt clinical features, this suggests that ADV might be an important cause of morbidity in RTRs. Keywords: Adenovirus, renal transplantation, real-time PCR, urine cytology Citation: Ahmed HM, Al-Obaidi AB, Hussein MR, Kadhim HS, Ghazi HF. Adenovirus infection in a sample of iraqi kidney transplant recipients: molecular and hematological study. Iraqi JMS. 2018; 16(3): 279-288. doi: 10.22578/IJMS.16.3.7